Effect of Mobile Phone Radiation on Reproductive System and Behavior Using Male Albino Mice - et al, Suhera Aburawi (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and objectives: This work was carried out to investigate the effect of mobile radiation on the behavior and reproductive system (histological study) in male albino mice. Methods: Twelve mice were divided into two groups. Group I: the control group was not exposed to mobile radiation (healthy mice); group II: mice were exposed to mobile radiation for one hour (active-ringing) per day for 90 days. At the end of the experiment, behavior scoring was carried out, followed by histological investigation of reproductive system. Results: In plus maze, anxiety measure, total lines crossed and total number of entries did not change compared to the control group. Also, in force swimming maze, the duration of immobility was not changed in mobile radiation exposed mice, compared to the control. Sperm morphology showed an increased in the percentage of abnormal sperm count in mice exposed to mobile radiation compared to the control mice group. Histological study showed that mice exposed to mobile phone radiation showed an increase of abnormal sperm shape compared to the control. A reduction of intraluminal spermatozoa, hypospermatogenic cells of seminiferous tubules was observed. Sperms also were very few inside the lumen of seminiferous tubules, and reduced number spermatogonia, spermatocytes, spermatid, and sertoli cells were observed. Conclusion: Exposure to mobile phone radiation has no effect on behavior; this indicates that it has no effect on the CNS for this duration of exposure. Histologically, this duration of exposure produced damage to testis structure and also in the morphology of sperms. Decrease in mobile phone usage each day keep the mind and body healthy.